The european union and Central and Eastern European countries on integration, foreign direct investment and international trade - Kyrkilis D.; Pantelidis P. (Selected readings on economies in transition, 2000)
The purpose of this paper is to analyze the effects of the integration process between the European Union (EU) and the Central and Eastern European Countries (CEEC) on the latter's international trade and foreign direct investment (FDI) position. The paper also examines the type of FDI, which is directed towards CEEC in relation to its integration with the European Union and its development process. Finally a mathematical model stating the relationship between trade flows, integration, FDI and economic growth is also presented.